STRATEGI COPING MAHASISWA DALAM MENGHADAPI TEKANAN AKADEMIK DI PERGURUAN TINGGI - Muhamad Suhardi; Meyldha Indah Lestari (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
ABSTRACK Academic pressure experienced by university students, including heavy coursework, academic performance demands, anxiety, and burnout, has increasingly become a significant issue affecting psychological well-being. Therefore, effective coping strategies are essential to help students manage these academic challenges. This study aimed to analyze students' coping strategies in dealing with academic pressure using a Systematic Literature Review (SLR) approach. The review followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines, including the stages of identification, screening, eligibility, and inclusion. Data were collected from scientific articles indexed in Google Scholar and Garuda published between 2021 and 2026. The selection process identified 25 articles that met the inclusion criteria. The findings revealed that emotion-focused coping was the most commonly used strategy, although excessive reliance on it was associated with increased anxiety. In contrast, problem-focused coping was found to be more adaptive because it effectively reduced academic stress and burnout. Furthermore, combining coping strategies with social support and spiritual factors enhanced students' psychological well-being. These findings highlight the importance of strengthening adaptive coping strategies through counseling services, stress management training, and social support programs in higher education institutions. ABSTRAK Tekanan akademik yang dialami mahasiswa di perguruan tinggi, seperti beban tugas, tuntutan prestasi, kecemasan, dan burnout, semakin meningkat serta berdampak pada kesejahteraan psikologis. Oleh karena itu, diperlukan strategi coping yang efektif untuk membantu mahasiswa mengelola tekanan tersebut. Penelitian ini bertujuan menganalisis strategi coping mahasiswa dalam menghadapi tekanan akademik melalui pendekatan Systematic Literature Review (SLR). Metode penelitian menggunakan pedoman Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) yang meliputi tahap identifikasi, screening, eligibility, dan inclusion. Data diperoleh dari artikel ilmiah yang terindeks di Google Scholar dan Garuda periode 2021–2026. Hasil seleksi menunjukkan 25 artikel memenuhi kriteria inklusi. Temuan menunjukkan bahwa emotion-focused coping merupakan strategi yang paling dominan, tetapi berpotensi meningkatkan kecemasan apabila digunakan secara berlebihan. Sebaliknya, problem-focused coping lebih adaptif karena mampu menurunkan stres dan burnout. Kombinasi strategi coping, dukungan sosial, dan faktor spiritual turut meningkatkan kesejahteraan psikologis mahasiswa. Temuan ini mengimplikasikan pentingnya penguatan strategi coping adaptif melalui layanan konseling, pelatihan manajemen stres, dan dukungan sosial di perguruan tinggi.